Evolutionary dynamics and geographical dispersal of Borrelia lusitaniae - Cirkovic, Valentina; Veinovic, Gorana; Stankovic, Daliborka; Mihaljica, Darko; Sukara, Ratko; Tomanovic, Snezana (Frontiers in Microbiology, 2024)
Background: Borrelia lusitaniae is a species within the complex Borrelia burgdorferi sensu lato, associated with lizards as reservoirs and Ixodes ricinus as its main vector. Borrelia lusitaniae is predominantly distributed in Central and Southeast Europe, and in countries of the Mediterranean basin, such as Portugal, Morocco, Tunisia, and Italy where this spirochete appears to infect vector ticks more frequently than other genospecies. Evolution of this zoonotic tick-borne microparasite is shaped by different environmental factors. Comprehensive phylogenetic analysis may give insight into how B. lusitaniae spreads to new geographic locations. Aim: We applied Bayesian statistical methods to B. lusitaniae multilocus sequence typing (MLST) data to study the migration routes of B. lusitaniae and its potential for further spread. Results: The discrete phylogeographic analysis placed origins of B. lusitaniae in Southeast Europe and identified at least two introductions of B. lusitaniae from Europe to North Africa. Estimated effective reproductive potential (Re), as a key indicator for a pathogen spread, suggested potential for further spread. Conclusion: The results of this study can provide beneficial information about the potential for further spread of B. lusitaniae in Europe and North Africa and estimation of necessity for the development of strategies to monitor and control Lyme borrelioses.